Estações de carregamento para carros elétricos alimentadas por usinas de microgeração fotovoltaica - Pereira, Lucas de Castro (2019)
The transport sector is one of the biggest responsibles for the emission of pollutants to the atmosphere. Thus, electric vehicles (EVs) appear as a clean alternative to mobility, provided that the energy used to fuel this type of vehicle has a non-polluting source as well. Combined with the fact that the quality of the infrastructure is one of the most relevant factors for the popularization of EVs, this paper presents the project of Charging Stations (CSs) for EVs powered by photovoltaic (PV) microgeneration plants for roads in Ceará. The opening chapters deal with PV generation in Brazil and Ceará - and characterize EVs from historical and market perspectives. In addition, several projections are analyzed that deal with how EVs can be established in the coming decades. According to the number of recharges possible, the installed powers of the CSs - 50, 62.5 and 75 kWp were defined, which are capable of meeting daily 5, 7 and 8 EVs in a scenario where full loads - from 0 to 100 % - are realized, called C1, and that offer a range for EVs of 300 km. In the scenario where only 20% loads are performed, called C2, it is possible to perform 27, 34 and 40 reloads, respectively. It was also analyzed the use of the CSs in Ceará highways that connect Fortaleza to tourist destinations for the formation of electrified roads, as well as in some itineraries within and from the capital of Ceará.